PERSEPSI SISWA TERHADAP GURU BK DALAM MEMBERIKAN PELAYANAN INFORMASI DI SMP 8 SAROLANGUN - Miftahul Rahmah; Hartini; Beni Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out students' perception of information services provided by Guidance and Counseling (BK) teachers at SMP 8 Sarolangun. The approach used in this study is quantitative with a descriptive design. The population of this study consisted of 101 students, and the sample used amounted to 50 students taken by purposive sampling technique. The research instrument used was a questionnaire consisting of 10 statements with a closed questionnaire that measured three aspects, namely information services, communication quality, and student satisfaction levels with BK teacher services. Validity: The instrument is considered valid if the validity of the content, the validity of the construct, and the empirical validity indicate that this questionnaire can measure the three aspects in question well. Reliability: The instrument is considered reliable if the Alfa Cronbach ≥ 0.70, and the test-retest and split-half tests show high consistency. The data obtained was then analyzed using descriptive analysis by calculating the percentage of student answer distribution. The results of the study showed that the average score for information services, communication quality, and satisfaction with BK teacher services were all in the Good category. The average score of the statement ranged from 2.54 to 3.36, indicating that students felt that the information provided was clear and useful, and felt comfortable when consulting. Student satisfaction is high with an average score of 2.82 to 2.84, and many are willing to recommend BK teachers to their friends. Based on these results, it is recommended that BK teachers continue to improve the quality of information delivery and communication in order to better meet the needs and expectations of students.